Changes in prescription of antidepressants and disability pension due to back pain, compared with other musculoskeletal and other somatic diagnoses: a cohort study in Sweden - Magnus Helgesson; Ellenor Mittendorfer-Rutz; Annina Ropponen; Pia Svedberg (BMJ Open)
Objectives The aim was to investigate differences in the prescription of antidepressants during the transition to disability pension (DP) comparing DP due to back pain with DP due to other musculoskeletal and DP due to other somatic diagnoses.Design A population-based cohort study with follow-up 3 years before and after the event. Estimated prevalence and adjusted ORs with 95% CIs for antidepressant prescription were computed for the 7-year window (ie, t-3 to t+3) around the DP by generalised estimating equations for repeated measures.Setting and participants This Swedish population-based nationwide study with registry data included individuals aged 18–64 years, with DP due to back pain (n=2011), DP due to other musculoskeletal (n=3548) or DP due to other somatic diagnoses (n=11 809).Primary outcome measures Prescription of antidepressants.Results Before DP, the prevalence of prescription of antidepressants was stable in DP due to back pain, but increased for the other DP groups. Similarly, the likelihood of prescription increased only marginally before DP due to back pain (ORs from 0.86 at t-3 to 1.10 at t-1), but clearly in DP due to musculoskeletal (from 0.42 to 1.15) and somatic diagnoses (from 0.29 to 0.98). Both prevalence measures and risks remained at the elevated levels after DP.Conclusions Pathways to DP due to musculoskeletal and somatic diagnoses seem to be partly driven by adverse mental health, which remains at a higher level after DP. The increasing prescription of antidepressants prior to DP suggests that special attention should be paid to mental health for prevention of DP. The period after DP needs attention to avoid deterioration of mental health.